HUMAN EMBRYONIC STEM CELL DERIVATIVE SUBRETINAL PIGMENT EPITHELIAL TRANSPLANTATION AS A TREATMENT FOR DRY-TYPE MACULAR - Muhammad Thifan Satyagraha; Andhwika Afif Fahrezi; Rafi Annisa Ulum; Gibran Chandra Syarif Hidayatullah (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2022)
Age-related Macular Degeneration (AMD), is the fourth disease which causes blindness in the world, will potentially increase in 2020. Therefore, alternative treatment is needed to be developed, such as Human Embryonic Stem Cell-derived Retinal Pigment Epithelium (hESC-RPE) transplantation in a subretinal layer. The purpose of this literature review is to identify AMD pathogenesis, especially dry type, to know the impact of hESC-RPE transplantation towards acuity of vision, and to understand its therapeutic effect, safety, also tolerability based on the literature cited. Articles were collected by google search engine through Pubmed, Sciencedirect, Proquest, and Springer link. Inclusion criteria are literature that was published between 2010-2020, clinical trial study, systematic review, and meta-analysis. the topic of these sources is focused on regenerative therapy in AMD patients. Whereas exclusion criteria are literature that published under 2010. According to our research, hESC-RPE transplantation in a subretinal layer can increase the acuity of vision in dry-type AMD patients by improving RPE pigmentation, which protects its photoreceptor cells. Safety and tolerability are proof that there are no abnormalities in proliferation and immunity. In conclusion, these findings are beneficial in the improvement quality life of AMD patients. Therefore, in the future, subretinal hESC-RPE can be effective in the alternative treatment of dry-typed AMD patients.